2013
DOI: 10.4103/0974-8237.121619
|View full text |Cite
|
Sign up to set email alerts
|

Clinical correlation of magnetic resonance imaging with symptom complex in prolapsed intervertebral disc disease: A cross-sectional double blind analysis

Abstract: Introduction:Low backache (LBA) is one of the most common problems and herniated lumbar disc is one of the most commonly diagnosed abnormalities associated with LBA. Disc herniation of the same size may be asymptomatic in one patient and can lead to severe nerve root compromise in another patient.Objective:To evaluate correlation between the clinical features of disc collapse and magnetic resonance imaging (MRI) finding to determine the clinical importance of anatomical abnormalities identified by MRI techniqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
20
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 26 publications
5
20
1
Order By: Relevance
“…In a few studies, the extent of agreement between the examiners was moderate (κ=0.51) and in test timings, it was excellent (κ=0.88) for the first examiner but good for the second examiner [11]. Similar to the present study, was the findings of Raininko and associates [15].…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…In a few studies, the extent of agreement between the examiners was moderate (κ=0.51) and in test timings, it was excellent (κ=0.88) for the first examiner but good for the second examiner [11]. Similar to the present study, was the findings of Raininko and associates [15].…”
Section: Discussionsupporting
confidence: 87%
“…One basic reason for the low agreement on the extent of "lumbar disk bulge" was due to not specifying the process of disk bulging by radiologist in 42% of cases. But in the present study (κ=0.75), both examiners assessed all the morphologic aspects of disk very carefully on the basis of defined criteria [11,12,15].…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…1,2,3,15,19 More than 88% of patients included in the current study were operated upon for pathologies affecting L 4-5 and L5-S1 levels (38.6% for L4-5 level and 50% for L5-S1 level) and this was similar to other reports. 1,19,20,21 In the current study, both patients' groups (the discectomy and fusion groups) showed statistically significant clinical and functional improvements in terms of changes in the mean pre-operative and post-operative VAS for low back pain and ODI values. However, comparison between both groups failed to reveal that any of them was significantly superior to the other regarding the forementioned parameters.…”
supporting
confidence: 88%
“…7,9,12,25,26,38 The majority of LBP is considered nonspecific, having no clear pathoanatomic cause 1,3 ; however, one specific cause of LBP is lumbosacral radiculopathy. 6,33 Known commonly as sciatica or lumbar radiculopathy, this condition has some unique defining characteristics. 24,34 Most commonly the result of a herniated disc, patients with sciatica typically complain of LBP and radiating lower extremity symptoms, which are often described as sharp, piercing, throbbing, aching, or burning, along with dermatomal paresthesia.…”
mentioning
confidence: 99%